Matrix Metalloproteinases and Their Tissue Inhibitors: an Evaluation of Novel Biomarkers in ANCA-Associated Vasculitis - Zakiyanov, O; Chocová, Z; Hrušková, Z; Hladinová, Z; Kalousová, M; Maličková, K; Vachek, J; Wurmová, P; Kříha, V; Zima, T; Tesař, V (Folia biologica, 2019)
Matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) may play an important role in both inflammation with subsequent fibrosis and in repair and healing in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). We evaluated the circulating levels of MMPs, including pregnancy-associated plasma protein A (PAPP-A), and TIMPs in patients with AAV. PAPP-A, MMP-2, MMP-3, MMP-7, MMP-9, TIMP-1, TIMP-2 and selected parameters were measured in 100 AAV patients (36 patients with active disease and 64 patients in remission) and 34 healthy subjects. The levels of MMP-2, MMP-3, MMP-7, MMP-9, TIMP-1, TIMP-2, and PAPP-A in AAV were all found to be different to those of the controls. The MMP-7 and PAPP-A concentrations were increased in active disease in comparison to the controls (MMP-7: 13 ±.7 vs. 2 ± 0.6 ng/ml, PAPP-A: 14 ± 18 vs. 6.8 ± 2.6 ng/ml, both P < 0.005). The MMP-2 and TIMP-2 levels were increased in remission when compared to the controls (MMP-2: 242 ± 50 ng/ml vs. 212 ± 26 ng /ml, TIMP-2: 82 ± 14 ng/ml vs. 68 ± 93 ng/ml) and to the active AAV (MMP-2: 242 ± 50 vs. 219 ± 54 ng/ml, TIMP-2: 82 ± 14 ng/ml vs. 73 ± 15 ng/ml, all P < 0.005). MMP-3, MMP-7, TIMP-1, and PAPP-A correlated with serum creatinine. The serum levels of MMPs, TIMPs and PAPP-A are all altered in AAV. MMP-2, MMP-7 and TIMP-2 appear to be promising markers in distinguishing active AAV from remission. MMP-3, MMP-7, TIMP-1, and PAPP-A are associated with kidney function in AAV. Further studies are needed to delineate the exact roles of circulating MMPs, TIMPs and PAPP-A in patients with AAV.
Keywords: ANCA-asociované vaskulitidy; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; Female; Aged; Matrix Metalloproteinases; dospělí; tkáňové inhibitory metaloproteinas; senioři; lidé; Biomarkers; Adult; matrixové metaloproteinasy; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; biologické markery; ženské pohlaví; Male; Middle Aged; Tissue Inhibitor of Metalloproteinases; mužské pohlaví